the reflection of Quranʹs proverbs in the values of Persianʹs civilization - عبد الحسن عبد حسام (Al-Adab Journal, 2018)
Hit Persian′s proverbs is considered an one of senior human values ​​that represent the culture and civilization of the Iranians. Not only the Persians taking them from the Quran on the hair and prose texts even inspired him to have some like them emerging, from here, the Persian proverbs inspired by the Quran has many of the senior human values. Follow researcher in his research presentation analytical approach descriptive terms divisible by three sections and as shown below: First research - the word (such as) from the perspective of linguistic terms included: 1.The term goes in the encyclopedia linguistic author Dhkhadda hit proverbs of the concept according to Briqaa The second topic - Supreme human values ​​in the Persian proverbs inspired by the Koran, containing: human value position to take advantage of hitting the Persian proverb. mentioned Persian proverb stated ideals inspired verse or Quranic text. mentioned Persian translation of the verse mentioned with her translator. Section III hit the Persian proverb emerging from the Quranic stories and contains two stories: 1.objections to the bne Israel such as dam Alas Researcher in revenue adopted his research on a variety of sources, including: Proverbs and the wisdom of Dhkhadda Dhkhaddh encyclopedia′s of language. Qur’an al magid had been translated by many known interpreter. proverbs and wisdom in works of poets. stories of proverbs . dictionary′s amed.